1994
DOI: 10.3354/meps109131
|View full text |Cite
|
Sign up to set email alerts
|

Winter abundance and distribution of Euphausia superba, E. crystallorophias, and Thysanoessa macrura in Gerlache Strait and Crystal Sound, Antarctica

Abstract: Euphausia superba and Thysanoessa macrura were the 2 most abundant euphausiids in the ice-covered waters west of the Antarctic Peninsula during July and August 1992. E. crystallorophias was limited to inshore waters. Detailed stratlfled sampling revealed that E. superba formed dense aggregations well below the ice, but was not inhabiting the ice itself In general, E. superba occupied the depth stratum from 15 to 130 m; few or no other zooplankton were found within E. superba swarms.7: rnacrura displayed a dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 28 publications
2
31
1
Order By: Relevance
“…[n summer, krill aggregations have been detected with acoustics in depressions within Arthur Harbor, near Palmer Station on Anvers Island (R . Ross, L. Quetin, T. Newberger, personal communication, 1993, 1994. Krill aggregations also have been observed with an ROY near the glacier face at the back of Arthur Harbor (G .…”
Section: Winter Distribution Patterns In Adult and Larval Krillmentioning
confidence: 96%
See 1 more Smart Citation
“…[n summer, krill aggregations have been detected with acoustics in depressions within Arthur Harbor, near Palmer Station on Anvers Island (R . Ross, L. Quetin, T. Newberger, personal communication, 1993, 1994. Krill aggregations also have been observed with an ROY near the glacier face at the back of Arthur Harbor (G .…”
Section: Winter Distribution Patterns In Adult and Larval Krillmentioning
confidence: 96%
“…Neither adults nor larvae were found associated with the ice. In winter 1992, Nordhausen (1994) inspected the underside of the ice in nearby bays with a video camera on an ROV, and also found no krill associated with the ice. Six cruises, (n=136 dives), oc-cwred during winters with adequate ice路cover 10 allow for a reasonable number of under-ice observations; pre-senee or absence of larval and adult krill within 1 m of the ice surface, and aggregation size(s) were nOled.…”
Section: 31mentioning
confidence: 99%
“…Surveys by remote operating vehicles (ROV) or SCUBA divers in diVerent regions of the Southern Ocean during winter (BransWeld Strait, Lazarev Sea, the WAP region) have only seldom observed adult krill associated with sea ice (Quetin et al 1994(Quetin et al , 1996Frazer et al 1997;Lawson et al 2008;Quetin and Ross 2009;Meyer et al 2010). Net surveys in the Gerlache Strait during winter found maximal krill abundance between 15 and 50 m depth (Nordhausen 1994;Zhou et al 1994). Fisheries research from diVerent regions in the Scotia Sea demonstrated that, in winter, the highest densities of krill were found between 80 and 240 m depth, whereas they aggregated at the surface and up to 60 m depth in spring and summer (Taki et al 2005).…”
Section: Body Lipid and Protein Utilisationmentioning
confidence: 99%
“…Feeding takes place wherever high amounts of food are available (open water, ice edge zone, under sea ice, etc.). At the onset of winter, when their metabolism is depressed, it was hypothesised from net and acoustic surveys that krill migrate inshore (Siegel 1989;Lascara et al 1999;Zhou et al 1994;Nordhausen 1994;Lawson et al 2008) to over-winter at depths over 200 m. Numerous aggregations were observed during winter in Marguerite Bay at depths greater than 150 m. This pattern, however, seems inconsistent throughout the years observed (Lawson et al 2008), demonstrating the highly variable nature of krill distribution during winter. In winter, adults feed opportunistically at low rates.…”
Section: Body Lipid and Protein Utilisationmentioning
confidence: 99%
“…Furthermore, in comparison to the well-studied time periods of austral spring and summer, when many antarctic regions are ice-free and more easily accessible to survey vessels, relatively few studies have examined krill distribution during winter (Siegel, 1989;Nordhausen, 1994;Ross et al, 1996;Lascara et al, 1999). This is particularly true for the continental shelf region in and around Marguerite Bay, west of the Antarctic Peninsula .…”
Section: Introductionmentioning
confidence: 99%